Anterograde injection of low-dose urokinase salvages free anterolateral thigh flap: A case report of safe and effective treatment. Issue 41 (October 2017) - Hsu, Shao-Yun; Cheng, Hsu-Tang; Manrique, Oscar; Hsu, Yung-Chang
Abstract: Rationale: A 54-year-old Taiwanese male came to our hospital presented with right retromolar mucoepidermoid carcinoma. Composite resection and right modified radical neck dissection were performed. We then use free anteral lateral thigh flap to reconstruct the defect. However, venous congestion was found 32 h after the surgery. Patient concerns: The main concerns of the patient is complete salvage of the free flap, and avoiding the secondary free flap harvesting and reconstruction surgeries. Diagnoses: Right retromolar mucoepidermoid carcinoma. Interventions: We report the case of a patient with an anterolateral thigh flap with venous perianastomosis thrombosis and intraflap microvascular thrombosis successfully salvaged using anterograde intra-arterial injection of low-dose urokinase (60, 000 U), without administering intravenous anticoagulation heparin during the postoperative period. Outcomes: The flap was completely salvaged 3 days after treatment. No other flap-associated or bleeding complications were noted. The intra-oral wounds around the flap completely healed without any post-ischemic complications. Lessons subsections: Although the ideal urokinase doses and delivery procedures for free flap salvage have not been developed thus far, our method maximizes the urokinase gradient in the flap, minimizes the total dose required for flap salvage, and ensures no systemic spread. Thus, compared with other thrombolytic agents, urokinase may be more effective and safe for free flap salvage. With more experience, a standardized dosage and procedure can be developed.